Test and measurement system for a microthruster system of a nanosatellite - Chia, Yong Xian (2014)
Miniaturized satellites which are fitted with microthrusters are gaining in popularity over the past few years. This is because of their simplified designs, small sizes and low weights that effectively reduce their production cost and increase their reliabilities. In order for those satellites to perform complex missions that require precise maneuverability, there is a need to develop a measurement system to measure the performance of the microthrusters. In this report, a torsional thrust stand with a magnetic damping system is designed and calibrated using an electrostatic calibrator. The calibration results showed that the thrust stand is able to measure thrust levels between 46.7μN and 892.71μN with a resolution of 4.67μN and an accuracy of 10% and below. Vaporising Liquid Microthruster, which is developed under the Undergraduate Satellite Programme in Nanyang Technological University, is used in the testing of this thrust stand. Although the thrusts of the microthruster lie outside the accurate measuring range of the thrust stand, they were obtained through extrapolation of the calibration curve and its specific impulse and thrust to weight ratio were found to be 5.64s and 0.0461 respectively. In addition, a levelling system with a 2% settling time of 49s is developed in attempt to keep the thrust stand perfectly horizontal during thrust measurements. A PID controller is used in the levelling feedback control loop to provide the desired control actions in the system. In order to further validate the thrust stand’s accuracy, future research such as using the torsional thrust stand to measure a known thrust from a known microthruster in both atmospheric and vacuum conditions can be carried out.